PHENOMENON OF DEMIKHOV. In the Sklifosovsky Institute (1960–1986). Doctor of Science – inexplicable oblivion – scientific horizons. The start of clinical transplantation in Russia (1964–1965) - S. P. Glyantsev (Трансплантология (Москва))
The article covers V.P. Demikhov work and activities at N.V. Sklifosovsky Research Institute for Emergency Medicine in 1964-1965. On May 28, 1964, V.P. Demikhov defended his Thesis for the Degree of the Candidate of Biological Sciences at the Biology Faculty of Moscow State University. But on the proposal of his opponents, Professor P.I. Androsov and Professor A.E. Gurvich, he was awarded the Degree of the Doctor of Biological Sciences at a second vote. On September 12, 1964, V.P. Demikhov was approved to the assignment of the sought Academic Degree by the Higher Attestation Commission at the Ministry of Higher and Secondary Special Education of the USSR. Unfortunately, the archival file of the Higher Attestation Commission on V.P. Demikhov's defending the Thesis has been lost. The present paper contains the recollections of M.M. Razgulov, an eyewitness of this Thesis defence, as well as the inexplicable facts on the missing information in the Academic Council documents of N.V. Sklifosovsky Institute for 1964-1965 about V.P. Demikhov's work and the activities of the Organ Transplantation Laboratory he headed in the Institute. It has shown that clinical transplantology in the USSR began on April 15, 1965, when the group of surgeons headed by B.V. Petrovsky performed a successful kidney transplant surgery in a human for the first time in this country. V.P. Demikhov did not participate in those events. In 1965, he was engaged in developing the problem of establishing a bank of functioning organs connected to a living organism.